Optimization of Drilling and Blasting Parameters During the Drifting of Underground Mine Workings - Almenov, Talgat; Zhanakova, Raissa; Shabaz, Din-Mukhammed; Orynbas, Arsen (Salehan Institute of Higher Education, 2026)
The study aims to scientifically substantiate optimal drilling-and-blasting (D&B) parameters for driving underground mine workings under complex geological and mining conditions at the Akzhal deposit. The work addresses the selection of explosive types and the rational depth, configuration, and design of cut boreholes, together with their blasting pattern (BP), to improve rock-mass stability, operational safety, and advance efficiency. The methodology combines an assessment of geological-technical conditions with a review of current blasting practice, mathematical and numerical modelling of blast-induced face breakage, and pilot-scale industrial trials supported by statistical analysis and techno-economic evaluation under routine production constraints and reporting. The results show that optimization of the BP increases the borehole utilization factor (BUF) from η = 0.85 to η = 0.98. The locally produced Granulite A6 is proven effective, reducing blasting costs by 1.5 times relative to AS-8 while preserving the required energy characteristics. Charge optimization improves excavation-contour quality, enhances fragmentation uniformity, and reduces overbreak; the most rational solution is a rhombic cut combined with Granulite A6. Scientific novelty lies in integrating geological-geomechanical analysis, 3D modelling in Micromine, and industrial validation. Practical relevance is confirmed by decreasing cycle costs from USD 538.85 to USD 489.38, improving BUF, and enhancing contour quality.